2005
DOI: 10.1093/ije/dyh401
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal risk factors for Caesarean section. Analyses of the ALSPAC cohort of 12 944 women in England

Abstract: A careful exploration of risk factors may allow us to identify reasons for the increasing rates of Caesarean section and the marked variation between institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
64
3
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 27 publications
26
64
3
8
Order By: Relevance
“…Apesar do estudo não ter investigado patologia específica, este conceito já está bem consolidado na prática obstétrica 27,28,29 , em particular a associação com diabetes (prévia ou gestacional) 14,29,30 .…”
Section: Discussionunclassified
“…Apesar do estudo não ter investigado patologia específica, este conceito já está bem consolidado na prática obstétrica 27,28,29 , em particular a associação com diabetes (prévia ou gestacional) 14,29,30 .…”
Section: Discussionunclassified
“…On the other hand, it is possible that increased use of antenatal services leads to increased medicalization of the pregnancy, including a greater openness to caesarean delivery. Overall, routine sonography in late pregnancy has not been shown to improve perinatal mortality 27 and there is limited sensitivity and specificity for 28 it is impossible to avoid the effect of physician preference in the face of specific clinical circumstances.…”
Section: Research Delivery Settings and Caesarean Section Rates In Chmentioning
confidence: 99%
“…7 In a study from England Patel et al, found similar risk factors but with a variation between institutions and concluded that a careful exploration of risk factors may allow us to identify reasons for the increasing rates of caesarean section and the marked variation between institutions. 8 The strength of present study was its novelty (not many such studies are available), the population size, heterogeneity and absence of confounding factors for rate of caesarean e.g. money and insurance.…”
Section: Discussionmentioning
confidence: 99%